Class comparison of middle class attributes in China and South Korea - Choi, Kyung Yun (2012)
Using urban household income and expenditure survey of China and South Korea, the paper examines traditional beliefs on the middle class in regards to economic growth. First belief is that the consumption of the middle class is an important source of domestic demands for goods and services. Second, unlike extravagant upper class, the thrifty middle class saves more for a stable life thereby providing sources for investment in the economy. Third, the middle class values and invests in human capital which becomes valuable input for the economy. From the class comparison of household budget allocation, the paper finds that those three economic expectations of the middle class are not specific characteristics of the middle class, but rather show intermediate attributes between those of the lower class and upper class considering the size of shares allocated to each purpose and changes over time. In addition, the results suggest that the consumption pattern of the middle class in China and South Korea has become similar over the past years.